In-depth snapshot of the equine subgingival microbiome. (May 2016) - Gao, Wenling; Chan, Yuki; You, Meng; Lacap-Bugler, Donnabella C.; Leung, W. Keung; Watt, Rory M.
Abstract: This study explored the range of bacterial taxa present within healthy subgingival (below the gum-line) niches in the horse oral cavity using 16S rRNA gene amplicon pyrosequencing. Pooled subgingival plaque samples were collected from approximately 200 sulcus sites from two horses (EQ1, EQ2) for analysis. A total of 14, 260 quality-filtered pyrosequencing reads were obtained, which were assigned to 3875 operational taxonomic units (OTUs; 99% identity cut-off); 1907 OTUs for EQ1 and 2156 OTUs for EQ2. Diverse taxa from 12 phyla were identified, including Actinobacteria (3.17%), Bacteroidetes (25.11%), Chloroflexi (0.04%), Firmicutes (27.57%), Fusobacteria (5.15%), Proteobacteria (37.67%), Spirochaetes (0.15%), Synergistetes (0.22%), Tenericutes (0.16%), GN02 (0.19%), SR1 (0.01%) and TM7 (0.37%). Many OTUs were not closely related to known phylotypes, and may represent 'equine-specific' taxa. Phylotypes corresponding to Gammaproteobacteria were abundant, including Actinobacillus spp. (8.75%), unclassified Pasteurellaceae (9.90%) and Moraxella spp. (9.58%). PCR targeting the Synergistetes and Spirochaetes phyla was performed, and resultant plasmid libraries of 16S rRNA gene amplicons (ca. 1480 bp) were Sanger sequenced. Twenty-six Spirochaetes OTUs, and 16 Synergistetes OTUs were identified (99% identity cut-off). These 'species-level' OTUs were assigned Equine Oral Taxon (EOT) numbers, whose phylogenies and taxonomy were comprehensively investigated, in conjunction with corresponding Synergistetes and Spirochaetes OTUs identified by pyrosequencing. The vast majority of Spirochaetes taxa belonged to the genus Treponema, which corresponded to 7 of the 10 human oral treponeme phylogroups. Other Spirochaetes taxa belonging to the Leptospiraceae family were observed; but many treponemes commonly implicated in animal hoof/foot and non-oral soft tissue infections; e.g. Treponema phagedenis, Treponema pedis, Treponema refringens, Treponema calligyrum ; were not identified here. Diverse Synergistetes taxa corresponding to oral clusters A and B were identified, which included Fretibacterium fastidiosum and Pyramidobacter piscolens . Taken together, our data reveals that equine subgingival plaque microbiota shares many similarities with the human, canine and feline oral microbiomes. Highlights: 12 Bacterial phya identified in equine subgingival (below the gumline) plaque. Diverse composition: similarities with human, canine and feline oral microbiomes. Spirochaetes and Synergistetes Equine Oral Taxon (EOT) were defined. Treponeme bacteria belonging to oral phylogroups 1–7 were identified. Certain treponemes associated with animal GI-tract and tissue infections not identified.